Factors Influencing Consumer Behavior: Using Paylater - Waskito Erdi, Tio (E-Jurnal Akuntansi, 2024)
Paylater provides convenience for the community, especially students, in meeting their consumptive needs. With the presence of paylater convenience, students can meet their consumptive needs quickly, safely, easily, and do not need to think about the availability of money to obtain goods or services. The use of paylater to meet consumptive needs provides convenience and flexibility in shopping, but also carries significant risks, especially if not used wisely. The study was conducted to measure what factors can influence consumptive behavior using paylater. The data collection technique used purposive sampling and obtained a population of 94 students. The test was carried out using the structural equation model (SEM) method with the SmartPLS test tool, the test was carried out by measuring the outer model and inner model. Based on the test results, it was found that financial literacy, prices, and security influenced consumptive behavior using paylater. Keywords: Financial Literacy; Price; Platform Security; Consumptive Nature; Paylater.